Computer-automated clinical technique for tinnitus quantification. - Henry JA; Fausti SA; Flick CL; Helt WJ; Ellingson RM (American Journal of Audiology, 2000)
This study addresses the need for uniformity in techniques for clinical quantification of tinnitus. Because automation can be an effective means to achieve standardization, this laboratory is developing techniques to perform computer-automated tinnitus testing. The present study was conducted to demonstrate the feasibility of obtaining reliable tinnitus measures using a fully automated system. A computer-controlled psychoacoustical system was developed to quantify tinnitus loudness and pitch using a tone-matching technique. Hearing thresholds were also obtained as part of the procedure. The system generated test stimuli and simultaneously controlled a notebook computer positioned in the sound chamber facing the patient. The notebook computer displayed instructions for responding and relayed response choices through on-screen 'buttons' that the patient touched with a pen device. Twenty individuals with tinnitus were evaluated with the technique over two sessions, and responses were analyzed for test-retest reliability. Analyses revealed good reliability of thresholds, loudness matches, and pitch matches. These results demonstrate that use of a fully automated system to obtain reliable measurements of tinnitus loudness and pitch is feasible for clinical application.